IT VALUE ESTIMATION USING PARTIAL ADJUSTMENT VALUATION WITH MVA DYNAMIC FACTOR - Nurhakim, Maiziah Azka; Abdurrahman, Lukman; Fauzi, Rokhman (Universitas Muhammadiyah Yogyakarta, 2022)
This paper discusses the substance of the value of IT in an IT-based company, namely PT. Telkom Indonesia. IT value is a value in financial benefits when capital expenditures include IT factors compared with capital expenditures that do not include IT. Nowadays, IT has become a business enabler that can improve the performance of business organizations efficiently and effectively in the company. The method used in this study is Partial Adjustment Valuation (PAV), which states that changes in output that occur in the production process are usually not exactly the desired one, so a Speed of Adjustment coefficient is needed to bridge the desired output with the actual output. This paper uses Dynamic Speed of Adjustment to calculate the fluctuates in IT values and the Market Value Added (MVA) factor to measure its dynamics. This study uses two calculation models: a three-factor model (K, L, and I) and a two-factor model (K and L) to prove the benefits of the IT value within a company. These measurements are split into two units: the currency unit (Performance Value) and the ratio unit (Performance Ratio). This paper leads to an understanding that the value of IT is real in improving business performance and refutes the paradox that states there is no relationship between IT investment and the size of the profits received by the company. Thus, the results of this study are open to studies that discuss the value of IT to develop further.